Nanotechnology-Based Face Masks: Transforming the Cosmetics Landscape - Vivek P. Chavda; Hetvi K. Solanki; Dixa A. Vaghela; Karishma Prajapati; Lalitkumar K. Vora (Micro)
The cosmetic market is constantly evolving and ever-changing, particularly with the introduction and incorporation of nanotechnology-based processes into cosmetics for the production of unique formulations with both aesthetic and therapeutic benefits. There is no doubt that nanotechnology is an emerging technology for cosmetic formulations. Among the numerous cosmetic items, incorporating nanomaterials has provided a greater scope and is commonly utilized in facial masks, hair products, antiaging creams, sunscreen creams, and lipsticks. In cosmetics, nanosized materials, including lipid crystals, liposomes, lipid NPs, inorganic nanocarriers, polymer nanocarriers, solid lipid nanocarriers (SLNs), nanostructured lipid carriers (NLCs), nanofibers, nanocrystals, and nanoemulsions, have become common ingredients. The implementation of nanotechnology in the formulation of face masks will improve its efficacy. Nanotechnology enhances the penetration of active ingredients used in the preparation of face masks, such as peel-off masks and sheet masks, which results in better effects. The emphasis of this review is mainly on the formulation of cosmetic face masks, in which the impact of nanotechnology has been demonstrated to improve the product performance on the skin.